Personal and situational predictors of everyday snacking: An application of temporal self‐regulation theory. Issue 4 (19th July 2017) - Elliston, Katherine G.; Ferguson, Stuart G.; Schüz, Benjamin
Abstract : Objectives: This study aims at testing predictions derived from temporal self‐regulation theory (TST) in relation to discretionary food choices (snacks). TST combines a motivational sphere of influence (cognitions and temporal valuations resulting in intentions) with a momentary sphere (encompassing social and physical environmental cues). This dual approach differs from current health behaviour theories, but can potentially improve our understanding of the interplay of personal and environmental factors in health behaviour self‐regulation. Design: A mixed event‐based and time‐based (Ecological Momentary Assessment) study in 61 adults aged between 18 and 64, with a BMI range between 18.34 and 39.78 ( M  =   25.66, SD  = 4.82) over two weeks. Methods: Participants recorded their food and drink intake for two weeks in real time using electronic diaries. Participants also responded to non‐consumption assessments at random intervals throughout each day. Momentary cues (individual, situational, and environmental factors) were assessed both during food logs and non‐consumption assessments. Motivational factors, past behaviour, and trait self‐regulation were assessed during baseline. Results: Multilevel logistic regression analyses showed that across all snack types, environmental cues and negative affect were associated with an increased likelihood of snacking. Perceiving a cost of healthy eating to occur before eating was associated with an increased likelihood of snacking, whereas intentions and self‐regulation were not. Conclusions: Discretionary food intake is largely guided by momentary cues, and motivational‐level factors, such as intention and self‐regulation, are less important in the initiation of discretionary food intake. Statement of contribution What is already known on this subject? Overweight and obesity are a result of prolonged periods of energy imbalance between energy intake and expenditure (Hill & Peters, 1998 ). One of the key behavioural determinants of energy imbalances results from food intake, specifically from discretionary food choices (snacking). Temporal self‐regulation theory (Hall & Fong, 2007 ) takes into account both deliberate and momentary influences on health behaviour, which is especially relevant to exploring the drivers of snacking. What does this study add? Offers new insight into the application of TST in explaining momentary eating behaviours. Snacking initiation is guided by momentary cues, not person‐level factors. Dietary interventions should acknowledge the momentary cues that are associated with snacking.